Examining the perceptions of tourism employees towards government policies for covid-19 recovery process - Chuah Shan Wen; Ellyana Stephanie Anak Galang; Esther Anak Morrison; Fahim Ahmad Ismail (2023)
In this study is conducted to examining the perceptions of tourism employees in the state of Kelantan towards government policies for COVID-19 recovery process. To obtain the best results, in this study, the researchers stated two objectives : (i) To identify government's policies regarding how to rebuild the tourism industry post-COVID-19 and (ii) To examine government’s plans to promote digital transition in the tourism industry post-COVID-19. The researchers will employ a method of in-depth interview sessions with employees of travel agencies located in Kota Bharu, Kelantan. This qualitative data collection method will involve interviews that include some significant questions in order for gaining rich data. Further data analysis will be conducted to achieve the objectives outlined in this study.